Synergistic degradation of PNP via coupling H2O2 with persulfate catalyzed by nano zero valent iron. Issue 35 (28th June 2019) - Du, Jiangkun; Wang, Yang; Faheem,; Xu, Tiantian; Zheng, Han; Bao, Jianguo
Abstract : Simultaneous activation of H2 O2 and persulfate by nanoscaled Fe 0 shows synergistic effect for degradation of p -nitrophenol with generating both hydroxyl and sulfate radicals in a wide initial pH range. Abstract : H2 O2 and persulfate (PDS) activated by iron are attracting much attention due to their strong oxidation capacity for the effective degradation of organic pollutants. However, they face problems such as requiring an acidic reaction pH and difficulty of Fe 2+ regeneration. In this study, the simultaneous activation of H2 O2 and persulfate by nanoscaled zero valent iron (nZVI) was investigated for the degradation of p -nitrophenol (PNP). The nZVI/H2 O2 /PDS oxidation system exhibited significantly higher reactivity toward PNP degradation than the systems with a single oxidant. A synergistic effect was explored between H2 O2 and PDS during nZVI-mediated activation, and the molar ratio of H2 O2 /PDS was a key parameter in optimizing the performance of PNP degradation. The nZVI/H2 O2 /PDS system could function well in a wide pH range, and even 95% PNP was removed at an initial pH 10, thus markedly alleviating the pH limitations of Fenton-like processes. Both hydroxyl radicals and sulfate radicals could be identified during H2 O2 /PDS activation, in which H + produced during PDS decomposition promoted H2 O2 activation. The increase of oxidant concentration could significantly enhance the PNP degradation, while the presence of HCO3 − and HPO4 2− exerted great inhibition. Furthermore, five degradation intermediates of PNP were detected and its degradation pathways in the nZVI/H2 O2 /PDS system were presented. This study reveals that the simultaneous activation of H2 O2 and PDS by nZVI is a promising advanced oxidation tool as an alternative to typical Fenton processes for recalcitrant pollutant removal.